THE POLITICAL ECONOMY OF POVERTY ALLEVIATION PROGRAM - faurani santi I singagerda; abshor Marantika (JURNAL ILMU MANAJEMEN SABURAI, 2015)
The experience from social impacts of the 1997 financial cristis that hit some countries in est and south-east asia, and recent general economic